Long-term health consequences of central precocious/early puberty (CPP) and treatment with Gn-RH analogue: a short update: Long term consequences of precocious puberty - Soliman, Ashraf T; Alaaraj, Nada; De Sanctis, Vincenzo; Hamed, Noor; Alyafei , Fawzia; Ahmed, Shayma (Acta Biomedica Atenei Parmensis, 2023)
Background: The relationship between precocious or early puberty and its treatment has received significant research attention, yielding diverse outcomes. This short review aims to comprehensively analyze and summarize research articles to elucidate the potential link between precocious or early pubertal onset (CPP) and crucial health factors. Methods: We conducted a systematic review of studies published from January 2000 to March 2023, sourced from databases of Medline, PubMed, Google Scholar and Web of Science. We assessed the relationship between CPP and final adult height (FHt), bone health, reproductive function, body mass index, metabolic and cardiovascular abnormalities, and increased cancer risk. Results: Upon reviewing and analyzing selected studies, the following key findings emerged: (a) treating CPP in girls before age 6-7 and in boys before age 9 improves FHt; (b) bone mineral density (BMD) decreases during GnRHa treatment but normalizes afterward, with no lasting effects on peak bone mass during puberty; (c) GnRH treatment does not negatively affect menstrual cycles; however, untreated CPP increases the risk of premature or early-onset menopause; (d) the incidence of PCOS/hyperandrogenemia may be slightly elevated in women with a history of CPP, but overall reproductive function remains largely unaffected; (e) earlier thelarche and menarche may enhance susceptibility to breast carcinogenesis; (f) CPP contributes to an increased risk of obesity and type 2 diabetes in both genders; (g) early menarche may slightly increase the risk of coronary heart disease and ischemic strokes and (h) early pubertal timing increases the risk of depression and anxiety disorders. Conclusion: Monitoring and early diagnosis of these conditions are of paramount importance for successful management.